Kinship Travel: Relatedness through International Tourism and Travel Networks - Cohen, Frayda; Speier, Amy; Frohlick, Susan (Anthropologica, 2015)
While genealogical, or roots tourism, in which people return to an ancestral homeland has been popular for some time, travel to create families is relatively new. These contemporary forms of what we are calling "kinship travel" are the central focus of this issue.